The effects of systemic immunomodulatory treatments on COVID‐19 outcomes in patients with atopic dermatitis: Results from the global SECURE‐AD registry. (12th October 2022) - Musters, Annelie H.; Broderick, Conor; Prieto‐Merino, David; Chiricozzi, Andrea; Damiani, Giovanni; Peris, Ketty; Dhar, Sandipan; De, Abhishek; Freeman, Esther; Arents, Bernd W. M.; Burton, Tim; Bosma, Angela Leigh‐Ann L.; et al.
Abstract: Background: Limited data are available on the effects of systemic immunomodulatory treatments on COVID‐19 outcomes in patients with atopic dermatitis (AD). Objective: To investigate COVID‐19 outcomes in patients with AD treated with or without systemic immunomodulatory treatments, using a global registry platform. Methods: Clinicians were encouraged to report cases of COVID‐19 in their patients with AD in the Surveillance Epidemiology of Coronavirus Under Research Exclusion for Atopic Dermatitis (SECURE‐AD) registry. Data entered from 1 April 2020 to 31 October 2021 were analysed using multivariable logistic regression. The primary outcome was hospitalization from COVID‐19, according to AD treatment groups. Results: 442 AD patients (mean age 35.9 years, 51.8% male) from 27 countries with strongly suspected or confirmed COVID‐19 were included in analyses. 428 (96.8%) patients were treated with a single systemic therapy ( n = 297 [67.2%]) or topical therapy only ( n = 131 [29.6%]). Most patients treated with systemic therapies received dupilumab ( n = 216). Fourteen patients (3.2%) received a combination of systemic therapies. Twenty‐six patients (5.9%) were hospitalized. No deaths were reported. Patients treated with topical treatments had significantly higher odds of hospitalization, compared with those treated with dupilumab monotherapy (odds ratio (OR) 4.65 [95%CI 1.71–14.78]), including after adjustment for confounding variables (adjusted OR (aOR) 4.99 [95%CI 1.4–20.84]). Combination systemic therapy which did not include systemic corticosteroids was associated with increased odds of hospitalization, compared with single agent non‐steroidal immunosuppressive systemic treatment (OR 8.09 [95%CI 0.4–59.96], aOR 37.57 [95%CI 1.05–871.11]). Hospitalization was most likely in patients treated with combination systemic therapy which included systemic corticosteroids (OR 40.43 [95%CI 8.16–207.49], aOR 45.75 [95%CI 4.54–616.22]). Conclusions: Overall, the risk of COVID‐19 complications appears low in patients with AD, even when treated with systemic immunomodulatory agents. Dupilumab monotherapy was associated with lower hospitalization than other therapies. Combination systemic treatment, particularly combinations including systemic corticosteroids, was associated with the highest risk of severe COVID‐19.